A combining design of precoder and equalizer based on shared redundancy to improve performance of ISI MIMO systems - Doanh, Bui Quoc; Quan, Do Thanh; Hiep, Pham Thanh; Hieu, Ta Chi (Wireless networks, 2019)
There have been a number of researches on block transmission systems via MIMO channels due to really high data transmission rate. However, because of the existence of inter-symbol interference (ISI) in the systems, guard intervals are added to eliminate the ISI, leading to a reduction in channel energy and bandwidth efficiency. In order to optimize these systems, there are many solutions in which a combining design of precoder and equalizer appears as a potential candidate. In this paper, a jointly optimal design for precoder and equalizer for ISI multiple input multiple output (MIMO) channels based on sharing redundancy is proposed. Theory analysis and simulation results demonstrate that the proposed design produces a significant improvement in the system performance such as a reduction in bit error rate, a decrease in channel energy loss and an increase in system throughput.